Distribusi Unsur dan Mineral pada Batuan Alterasi Illit-Serisit±Biotit Sekunder di Daerah Sumbersari - Afri Tri Kristanto (Retii, 2021)
The Kulonprogo Mountains as part of the magmatism path of the southern mountains which have mineral potential with small to large economic value. Epithermal mineralization has previously been found in the Kokap, Gunung Gupit – Menoreh, and Bagelen – Gunung Agung areas. This study identifies mineralization in the central-proximal facies of the Purba Ijo Volcano in Sumbersari, Kaligesing, Purworejo by looking at the geological conditions and distribution patterns of minerals in alteration rocks to provide data and information on geological phenomena in the study area. The research was conducted using literature study, data collection and observation, laboratory work, as well as interpretation and research evaluation. The geological condition of the study area is in the central – proximal facies of Khuluk Gajah which consists of andesite lava intruded by microdiorite, quartz microdiorite, diorite, andesite, basaltic andesite, and covered with Jonggrangan limestone. Many intrusions are supported by structures that develop around the microdiorite intrusion. Mineralization develops associated with porphyry type I guess with stockwork and sheeted vein textures, with vein types A, AB, and D. The final phase of alteration is sericite, illite, kaolinite, and pyrite dissemination which shows overprint by the epithermal system. In the LP2B sample XRD analysis shows an epithermal process that enters the porphyry body. XRF micro-analysis showed a diffuse pattern of altered minerals with a predominance of Si and heavy minerals and relatively clustered sulfides with a predominance of Fe and Cu. The relatively dominant S and Si elements in each vein are interpreted as being carried by the fluid that forms the vein.